Show that Pr(X = x; Y = y) = Pr(X = x) Pr(Y = y) if X and Y are independent. HINT: use the deÖnition of condition
If X and Y are independent, show sigma xy = 0: Hint: Write out one of the forms of covariance and then use the property shown in the previous question
Recently Asked Questions
- how can we derive the demand equation from the given graph. Problem 4.
- Please refer to the attachment to answer this question. This question was created from Homework 2_AGEC 2003.pdf. Additional comments: "I don't understand how
- How many international and regional UN Conventions are there regarding women's human rights? Please explain.